2012
DOI: 10.1210/en.2012-1818
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Nucleotide Transporter-Mediated ATP Release Regulates Insulin Secretion

Abstract: Extracellular ATP plays a critical role in regulating insulin secretion in pancreatic β cells. The ATP released from insulin secretory vesicles has been proposed to be a major source of extracellular ATP. Currently, the mechanism by which ATP accumulates into insulin secretory granules remains elusive. In this study, the authors identified the expression of a vesicular nucleotide transporter (VNUT) in mouse pancreas, isolated mouse islets, and MIN6 cells, a mouse β cell line. Immunohistochemistry and immunoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 38 publications
3
58
0
1
Order By: Relevance
“…SLC17A9 Localization in Lysosomes-SLC17A9 reportedly localizes in secretory vesicles/granules (3)(4)(5). Our pharmacology data obtained using isolated lysosomes suggest that lysosomal membranes contain substantial amounts of SLC17A9 protein.…”
Section: Inhibition Of Atp Transport Across the Lysosome Membrane By mentioning
confidence: 70%
See 2 more Smart Citations
“…SLC17A9 Localization in Lysosomes-SLC17A9 reportedly localizes in secretory vesicles/granules (3)(4)(5). Our pharmacology data obtained using isolated lysosomes suggest that lysosomal membranes contain substantial amounts of SLC17A9 protein.…”
Section: Inhibition Of Atp Transport Across the Lysosome Membrane By mentioning
confidence: 70%
“…SLC17A9 reportedly functions in insulin secretion through vesicular ATP release in ␤ cells (5), in exocytosis of ATP-enriched vesicles in biliary epithelial cells (25), and in exocytosis of ATP-enriched vesicles during T cell activation (4). However, the identities of the ATP-containing vesicles in these studies are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that insulin granules contain similar concentrations of ATP and ADP [3], suggesting that ] i , and the magnitude of ATP-release events was increased by glucose. This could result from intragranular ATP accumulation via granule-resident vesicular nucleotide transporter [25]. It should be noted, however, that in intact rodent islets extracellular ATP plays an important role in synchronising the electrical and Ca 2+ responses among beta cells within and between islets through the induction of Ca 2+ release from InsP 3 -sensitive stores [26][27][28], in addition to stimulating exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Exocytotic mechanisms involve ATP storage and Ca 2+ -regulated exocytotic release and SLC17A9 protein has been identified as a vesicular nucleotide transporter (VNUT) that plays a key role in ATP exocytosis [13]. VNUT expression has been detected in different types of cells [13][14][15][16][17][18][19]; however, its presence in corneal and conjunctival epithelial cells remains elusive.…”
Section: Introductionmentioning
confidence: 99%